Ocular manifestations of feline viral diseases - Stiles, Jean (Vet J, 2014)
Feline viral diseases are common and cats can be presented with a variety of clinical manifestations. Ocular disease associated with viral pathogens is not unusual, particularly with viruses causing upper respiratory tract disease in cats, such as feline herpesvirus type 1 and feline calicivirus. These agents mainly cause ocular surface disease. Other viruses, such as feline immunodeficiency virus and feline coronavirus, can cause uveitis, while feline leukemia virus can induce ocular lymphosarcoma. This review covers the most common viral pathogens of cats that cause ocular manifestations, the specific features of the ocular diseases caused by these viruses and therapeutic recommendations.